Autologous Marrow Mesenchymal Stem Cell Driving Bone Regeneration in a Rabbit Model of Femoral Head Osteonecrosis - Ilenia Mastrolia; Andrea Giorgini; Alba Murgia; Pietro Loschi; Tiziana Petrachi; Valeria Rasini; Massimo Pinelli; Valentina Pinto; Francesca Lolli; Chiara Chiavelli; Giulia Grisendi; Maria Cristina Baschieri; et al. (MDPI AG, 2022)
Osteonecrosis of the femoral head (ONFH) is a progressive degenerative disease that ultimately requires a total hip replacement. Mesenchymal stromal/stem cells (MSCs), particularly the ones isolated from bone marrow (BM), could be promising tools to restore bone tissue in ONFH. Here, we established a rabbit model to mimic the pathogenic features of human ONFH and to challenge an autologous MSC-based treatment. ON has been originally induced by the synergic combination of surgery and steroid administration. Autologous BM-MSCs were then implanted in the FH, aiming to restore the damaged tissue. Histological analyses confirmed bone formation in the BM-MSC treated rabbit femurs but not in the controls. In addition, the model also allowed investigations on BM-MSCs isolated before (ON-BM-MSCs) and after (ON+BM-MSCs) ON induction to dissect the impact of ON damage on MSC behavior in an affected microenvironment, accounting for those clinical approaches foreseeing MSCs generally isolated from affected patients. BM-MSCs, isolated before and after ON induction, revealed similar growth rates, immunophenotypic profiles, and differentiation abilities regardless of the ON. Our data support the use of ON+BM-MSCs as a promising autologous therapeutic tool to treat ON, paving the way for a more consolidated use into the clinical settings.